2009
DOI: 10.1007/s00259-009-1113-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidental head and neck 18F-FDG uptake on PET/CT without corresponding morphological lesion: early predictor of cancer development?

Abstract: Elevated/asymmetric head and neck FDG accumulation without a correlating morphological lesion can frequently be found and does not predict cancer development. In populations in which goitre is endemic, FDG uptake by the thyroid is common and not associated with thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…However, all the ultrasound scans were performed by 2 experienced consultant radiologists with an interest in thyroid disease who did not find a distinct focal suspicious abnormality worthy of biopsy in the remaining 17 cases. In contrast to other studies, Heusner et al [14] detected FDG uptake in the thyroid gland in 31% of patients, mostly symmetric, but there was not a single Incidental findings on PET/CT scans case of confirmed thyroid malignancy. This study concluded that, for populations in which thyroid goitre is endemic, FDG uptake by the thyroid is common and not associated with thyroid cancer.…”
Section: Incidental Findings On Pet/ct Scanscontrasting
confidence: 43%
See 1 more Smart Citation
“…However, all the ultrasound scans were performed by 2 experienced consultant radiologists with an interest in thyroid disease who did not find a distinct focal suspicious abnormality worthy of biopsy in the remaining 17 cases. In contrast to other studies, Heusner et al [14] detected FDG uptake in the thyroid gland in 31% of patients, mostly symmetric, but there was not a single Incidental findings on PET/CT scans case of confirmed thyroid malignancy. This study concluded that, for populations in which thyroid goitre is endemic, FDG uptake by the thyroid is common and not associated with thyroid cancer.…”
Section: Incidental Findings On Pet/ct Scanscontrasting
confidence: 43%
“…Heusner et al [14] examined the intensity and symmetry of FDG uptake at 4 sites (Waldeyer's ring, oral floor, larynx and thyroid) in 590 patients without a head or neck malignancy, inflammation or a correlating morphological lesion on a fully diagnostic CT scan to determine whether the increased FDG uptake indicated the development of a head and neck malignancy. Increased FDG uptake was present in one of the sites of interest in 60% of cases.…”
Section: Incidental Findings On Pet/ct Scansmentioning
confidence: 99%
“…A variation of 3.2 was considered clinically relevant using an average score of 10 with an SD of 3 in a referred population studied with a standard method (17). To obtain a strength of 90%, it would have been necessary to recruit 22 patients; the available number of patients in our study (34) was a sufficient number to perform the study.…”
Section: Discussionmentioning
confidence: 99%
“…Although increased, unilateral glucose metabolism can be caused by inflammatory processes or asymmetrical focal muscular activity and has to be considered as nonspecific in most cases, it can mimic malignant processes (26,27). Heusner et al (27) demonstrated that unilateral or asymmetrical muscular uptake without a morphologic correlate is no predictor for malignancy. Still, its presence can be problematic in some cases, particularly if the quality of morphologic images is impaired by motion In the thyroid, focal tracer uptake is problematic.…”
Section: Discussionmentioning
confidence: 99%